Ґард - могильник маріупольського типу на Південному Бузі - Товкайло, М.Т.; Фоменко, В.М. (Археологія, 2015)
Стаття вводить до наукового обігу матеріали відкритого нещодавно в Побужжі на території знаменитого поселення Ґард могильника маріупольського типу. Також визначає місце могильника в мезоліті–ранньому неоліті Південно-Східної Європи. Новый могильник мариупольского типа открыт в 2011 г. и исследован авторами в 2013 г. на территории извест ного многослойного поселения Гард, находящегося на правом берегу Южного Буга на расстоянии 2,5 км к югу от с. Богдановка Доманевского рна Николаевской обл.
Могильник расположен внутри мощной каменной постройки, возведенной вокруг него. По данным стратигра фии, он залегает непосредственно под ранненеолитическим культурным слоем (БДК), который отражает начальный этап неолитизации региона. Все захоронения опущены с поверхности дерновоалювиальной супеси — среднего генетического горизонта (Нр) третьей голоценовой почвы, составленной на аллювиальных отложениях надпоймен ной террасы. На поверхности этого же литологического образования залегают остатки каменной постройки.
Исследована одна компактная группа из 15 захоронений, расположенных в один ряд. Ямы отдельных захо ронений, залегающие в три яруса, сливаются в одну общую «траншею». Все покойники положены вытянуто на спине, головами в одном направлении поперек «траншеи» и параллельно линии берега. Все они головами на правлены против течения реки. Погребальный инвентарь очень беден. В некоторых погребениях зафиксированы следы красной охры.
По данным стратиграфии, могильник мариупольского типа на Гарде может относиться к позднему мезолиту, возможно, к самым истокам раннего периода неолита. В то же время полученные в 2014 г. в Киевской лабора тории по костям исследуемого могильника даты оказались на два тысячелетия позже ожидаемых, что противо речит археологическим данным. На возможную датировку могильника в пределах второй половины vii — первой четверти vi тыс. до н. э. указывают две даты (Ки14796 и Ки14797), полученные в той же лаборатории в 2008 г., первая из которых совпадает с датировкой Васильевского 2 и Марьевского позднемезолитических могильников, близких к Гарду по обряду захоронения. Между тем Гардовский могильник обладает определенной спецификой, отличающей его от синхронных могильников Надпорожья.
Поиски аналогов каменным сооружениям Ґардовского могильника приводят нас в Железные Ворота на Дунае. Здесь в ходе раскопок могильников Падина и Хайдуцкая Воденица были исследованы так называемые каменные сооружения некрополя. Могилы, связанные с этими каменными сооружениями, располагались рядом с ними.
Краткий обзор мезолитических и ранненеолитических могильников БалканоДунайского региона показы вает, что между могильниками Железных Ворот (Падина, Хайдуцкая Воденица), Побужья (Гард) и Надпорожья (Васильевка 2, Марьевка) есть немало общего: расположение могильников, размещение погребений, положение скелетов, инвентарь и т.д. Выглядит так, что Гард занимает промежуточное положение между Надпорожьем и Же лезными Воротами, и не только географически. Сохраняя большинство признаков могильников мариупольского типа Надпорожья, он по некоторым из них ближе к названным погребальным памятникам Железных Ворот. A new Mariupol type burial ground was discovered in 2001 and studied by the authors in 2013 at the territory of Gard, a famous multilayer settlement situated on the left bank of the South Buh River at a distance of 2,5 km from Bohdanivka village of Domanivka Region in Mykolayiv oblast.
The burial ground is situated inside the intense stone housing surrounding it. according to stratigraphic data, it lays directly below the Early neolithic cultural layer (BuhDnister culture) which reflects the initial stage of neolithization of the region. all the burials are sunk from the surface of alluvial turf sandy loam, middle genetic horizon (hp) of the third holocene soil constituted on alluvial deposits of the terrace above the drain. The remains of stone structures lay on the surface of the same lithologic formation.
Studied is a compact group of 15 burials formed up in a rank. Pits of some burials situated on three tiers flow together in one common «trench». all the burials are extended, have the same directions of the heads across the «trench», and are parallel to the bank line. all of the dead are directed with their heads against the river’s stream. The funeral inventory is scarce. in some burials the traces of red ochre are recorded.
according to stratigraphic data, the Mariupol type burial ground at Gard can be referred to the late Mesolithic age, perhaps to the very beginnings of the early period of the Mesolithic age. at the same time, the dates obtained in kyiv laboratory based on the bones from the burial ground appeared to be two millennia later than expected and contradict the archaeological data. Probable dating of the burial ground within the period from the second half of the 7th millennium to the first half of the 6th millennium BC is indicated by the two dates (Ки14796 and Ки14797) obtained in the same laboratory in 2008, first of which coincides with dating of the late Mesolithic vasylivka 2 and Maryivka burial grounds close to Gard by the funeral customs. Meanwhile, Gard burial ground has its peculiarity distinguishing it from the synchronous burial grounds in nadporizzhia.
Search for analogies of stone structures at Gard burial ground led the authors to the iron Gate in the Danube River region where stone building was widely used in funeral customs of the population in the Mesolithic and the Early neolithic ages. here, during the excavations of Padina and hajducka vodenica burial grounds, various «stone structures at necropolis» were studied. Graves related to these stone structures were situated close to them. The burials were exclusively extended and the buried were oriented parallel to the Danube River with their heads down the flow. hajducka vodenica is also peculiar for group burials in funeral customs, which are common at Gard, as well as at all the burial grounds of Mariupol type.
a brief review of the Mesolithic and the Early neolithic burial grounds at Balkan and Danube regions shows that burial grounds at the iron Gate (Padina and hajducka vodenica), the Buh River region (Gard) and nadporizzhia (vasylivka 2 and Maryivka) have much in common. namely, the situation in the mountain gorge in the region of rapids and islands; extended burials made in oval pits separately or in groups; burials formed up in ranks within one, two or more tires; scarce inventory with total lack of ceramics; sporadic ochre usage. it looks like Gard mediates between nadporizzhia and the iron Gate, and not only geographically. Preserving most of features of Mariupol type burial grounds in nadporizzhia, it is closer to the listed burial sites of the iron Gate by some peculiarities: situated at the terraces above the drains on the settlements’ territories, stone building is used in burial customs, and the buried are oriented along the thread of stream.